Characterization of a conditional interleukin‐1 receptor 1 mouse mutant using the Cre/LoxP system. Issue 4 (18th January 2016) - Abdulaal, Wesam H.; Walker, Catherine R.; Costello, Ryan; Redondo‐Castro, Elena; Mufazalov, Ilgiz A.; Papaemmanouil, Athina; Rothwell, Nancy J.; Allan, Stuart M.; Waisman, Ari; Pinteaux, Emmanuel; Müller, Werner
Abstract : We describe a conditional IL‐1 receptor 1 (IL‐1R1) mouse mutant (IL‐1R1 fl/fl ), which allows cell/tissue‐specific genetic inhibition of all IL‐1R1 isoforms after Cre‐mediated recombination as well as a new IL‐1R1 deficient mouse in which all IL‐1R1 isoforms are deleted. These mice will provide a tool to study the cellular IL‐1 network. Abstract : IL‐1 is a key cytokine known to drive chronic inflammation and to regulate many physiological, immunological, and neuroimmunological responses via actions on diverse cell types of the body. To determine the mechanisms of IL‐1 actions as part of the inflammatory response in vivo, we generated a conditional IL‐1 receptor 1 (IL‐1R1) mouse mutant using the Cre/LoxP system (IL‐1R1 fl/fl ). In the mutant generated, exon 5, which encodes part of the extracellular‐binding region of the receptor, is flanked by LoxP sites, thereby inactivating the two previously described functional IL‐1R1 gene transcripts after Cre‐mediated recombination. Using keratin 14‐Cre driver mice, new IL‐1R1 deficient (−/−) mice were subsequently generated, in which all signaling IL‐1 receptor isoforms are deleted ubiquitously. Furthermore, using vav‐iCre driver mice, we deleted IL‐1 receptor isoforms in the hematopoietic system. In these mice, we show that both the IL‐17 and IL‐22 cytokine response is reduced, when mice are challenged by the helminth Trichuris muris . We are currently crossing IL‐1R1 fl/fl mice with different Cre‐expressing mice in order to study mechanisms of acute and chronic inflammatory diseases.